Tumor necrosis factor-α-activated mesenchymal stem cells accelerate wound healing through vascular endothelial growth factor regulation in rats - Aditya Nugraha; Agung Putra (Faculty of Medicine, Universitas Trisakti, 2018)
BackgroundWounds are areas of physical or thermal damage of the epithelial layer of skin or mucosa. The wound healing process consists of hemostasis, inflammation, proliferation, and remodeling. Mesenchymal stem cells (MSCs) play a role in wound healing by suppressing potent pro-inflammatory molecules, such as tumor necrosis factor-α (TNF-α), leading to macrophage polarization from the pro-inflammatory type to the pro-regeneration type characterized by increasing vascular endothelial growth factor (VEGF) production. MSCs are able to increase VEGF level in-vivo correlated with collagen synthesis. The objective of this study was to assess the role of TNF-α-activated MSCs on VEGF in rat wounds. MethodsAn experimental animal study with post-test only control group design was performed involving 24 Wistar rats. The rats were randomized into four groups consisting of one control (K) and three treatment groups (P) (activated MSCs at doses of 3x105, 6x105, and 12x105 cells, respectively). The measurement of VEGF levels was done using ELISA assay while the collagen analysis was performed by light microscopy. One way ANOVA and Post Hoc LSD were used to analyze the data.ResultsThe results showed a significant increase in VEGF levels (p <0.05) on day 3 and then a significant decrease on day 5 along with a significant increase in the amount of collagen on day 7 (p<0.05).ConclusionThis study demonstrated that TNF-α-activated MSCs were able to regulate VEGF levels and collagen synthesis in wound healing in rats. The molecular mechanism by which TNF-α-activated MSCs stimulate cutaneous wound healing should be clarified further.